Impact of smoking on dendritic cells in patients with oral squamous cell carcinoma - Heron STÄHELIN; Ana Lucia Noronha FRANCISCO; Fernanda Viviane MARIANO; Luiz Paulo KOWALSKI; Rogério GONDAK (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Smoking has been shown to alter innate and adaptive immune responses and is directly associated with the onset of oral squamous cell carcinoma (OSCC). The purpose of this study was to evaluate the effect of cigarette smoke exposure on dendritic cells (DCs) from OSCC patients. CD1a and CD83 antibodies were used to identify immature and mature DCs, respectively, by immunohistochemistry in OSCC samples of 24 smokers and 24 non-smokers. Density of DCs was calculated in intra and peritumoral areas. Clinical and microscopic findings were reviewed and analyzed for all patients. Smokers with OSCC had a lower density of intra and peritumoral DCs when compared to non-smokers. Tumors classified as moderately/poorly differentiated had lower peritumoral CD1a+ DCs than well-differentiated tumors (p < 0.001). Smoking contributed to a depletion of immature and mature DCs in the OSCC.